Risks posed by obesity to body-surface narrowband wireless communication - Yang, Xiaodong; Zhang, Qing; Yang, Shuyuan; Ren, Aifeng; Zhang, Zhiya; von Deneen, Karen M; Hao, Yang (Chinese science bulletin, 2014)
Little work has been done on the effect of being overweight on the wireless narrowband radio propagation of wearable medical instruments. In this paper, by applying a finite-difference time-domain technique and a statistical learning method, the authors find that being overweight might be an obstacle to body-surface wireless communication. The findings have certain instructive meanings for those engineers who are designing on-body medical instruments for patients, especially those patients who are overweight.